How Online Teams with Diverse Backgrounds Worked to Excel: Findings from an International eTournament - Lau, Martin; Vuthaluru, Rupa; Mui, Lawrence; Kerrigan, Simon; Kwong, Theresa; Law, Lisa; Wong, Eva Y. W.; Gibson, David (Frontiers in Education, 2021)
A tide of changes with technological advances at its centre has allowed more efficient and productive synchronous and asynchronous collaborations among dispersed individuals across the globe in recent years. Working effectively in virtual teams of individuals with diverse backgrounds is thus critical for students to succeed in the 21st century. However, relevant training for international collaboration is lacking in the higher education system. The research team examined data from a project aimed to heighten students’ multidisciplinary and multicultural competencies via a team-based, international eTournament organised in 2019 and enhanced and repeated in early 2020 featuring the 17 Sustainable Development Goals (SDGs) of the United Nations. Students were teamed up according to a mechanism, to ensure diversity in each virtual team and mimic the real practice in many workplaces. A two-stage “strategise-play” approach was deployed with activities carried out entirely online. Team members first got to know each other, built up their teams and formulated their strategies for the next stage. In the second stage, the virtual teams competed with one other on a gamified learning platform called PaGamO by answering questions related to the SDGs. About 240 students (2019) and 420 students (2020) participated. Various sets of quantitative and qualitative data were collected, including student chat histories, focus group interviews, data analytics from PaGamO recording how the students progressed in the game, as well as the pre- and post-game surveys. This article focuses on the chat histories of students from the top-5 and bottom-5 teams of the 2019 and 2020 eTournaments. The results provide evidence that the high performing teams took a different gaming approach from the low performing teams in such areas as team building and game strategy deployment.